Efektivitas Ekstrak Daun Pepaya secara Invitro terhadap Colletotrichum gloeosporioides Penyebab Penyakit Antraknosa pada Tanaman Cabai: Effectiveness of papaya leaf extract in vitro against Colletotrichum gloeosporioides, the pathogen of the anthracnose disease on red pepper - arneti, Arneti; Liswarni, Yenny; Edriwilya, Rifa (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2020)
Papaya leaf (Carica papaya Linnaeus) is one of the sources of botanical fungicides that is known to have an ability in inhibiting Colletotrichum gloeosporioides growth. The aim of the study was to determine the effectiveness of papaya leaves extract to suppress of C. gloeosporioides growth that caused anthracnose disease of red pepper (Capsicum annuum Linnaeus) in vitro assay. The study was done in a Completely Randomized Design (CRD) with five concentration levels of papaya leaves extract and control (1%, 2%, 3%, 4%, 5%, and control). The parameters were colony growth, colony area, wet weight, dry weight, and conidia number (per ml of suspension). The data obtained were analyzed by ANOVA and LSD tests at 5% significance level. The results showed that the application of papaya leaves extract with different concentrations could suppress the growth of C. gloeosporioides, the pathogen of anthracnose disease in chili. The higher the concentration of papaya leaves extract given, the higher its effectiveness in suppressing the growth of C. gloeosporioides. Application at the 5% concentration was the most effective inhibiting the conidia formation (82.5%), followed by inhibiting the expansion of the colony (64.04%), reducing wet weight (45.16%) and dry weight (54.16%). Keywords: Anthracnose, botanical fungicides, Capsicum annuum, concentration, growth inhibitor